Discovering novel neuroactive drugs through high-throughput behavior-based chemical screening in the zebrafish - Bruni, Giancarlo; Lakhani, Parth; Kokel, David (Frontiers in Pharmacology, 2014)
Most neuroactive drugs were discovered through unexpected behavioral observations. Systematic behavioral screening is inefficient in most model organisms. But, automated technologies are enabling a new phase of discovery-based research in central nervous system (CNS) pharmacology. Researchers are using large-scale behavior based chemical screens in zebrafish to discover compounds with new structures, targets and functions. These compounds are powerful tools for understanding CNS signaling pathways. Substantial differences between human and zebrafish biology will make it difficult to translate these discoveries to clinical medicine. However, given the molecular genetic similarities between humans and zebrafish, it is likely that some of these compounds will have translational utility. We predict that the greatest new successes in CNS drug discovery will leverage many model systems, including in vitro assays, cells, rodents, and zebrafish.